1999
DOI: 10.1007/s004649901152
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of lymphocele after kidney transplantation

Abstract: Laparoscopic drainage of posttransplantation lymphocele is a relatively simple method for treating this complication, although it bears the burden of an increased incidence of urinary tract lesions, as confirmed by a review of the literature. The major advantage of the laparoscopic approach is the absence of postoperative ileus with the opportunity to continue the enteral immunosuppressive regimen and a lower recurrence rate. These data suggest that laparoscopic lymphocele treatment might be considered the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Hsu et al [8], in a multicenter review of experienced centers, found a complication rate of 5% with only a single urinary tract (bladder) injury. Cadrobbi et al [3], in a retrospective review of published cases, found a 7% incidence of urinary tract injury (renal pelvis, ureter, bladder) with laparoscopic fenestration, but the rate was lower in centers with significant experience. Interestingly, lymphocele recurrence requiring reoperation is more common following open surgery compared to laparoscopy [3].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hsu et al [8], in a multicenter review of experienced centers, found a complication rate of 5% with only a single urinary tract (bladder) injury. Cadrobbi et al [3], in a retrospective review of published cases, found a 7% incidence of urinary tract injury (renal pelvis, ureter, bladder) with laparoscopic fenestration, but the rate was lower in centers with significant experience. Interestingly, lymphocele recurrence requiring reoperation is more common following open surgery compared to laparoscopy [3].…”
Section: Discussionmentioning
confidence: 96%
“…Cadrobbi et al [3], in a retrospective review of published cases, found a 7% incidence of urinary tract injury (renal pelvis, ureter, bladder) with laparoscopic fenestration, but the rate was lower in centers with significant experience. Interestingly, lymphocele recurrence requiring reoperation is more common following open surgery compared to laparoscopy [3]. Our experience confirmed this finding as our recurrence rate for open drainage was 11% compared to 4% for laparoscopy, although this is not statistically significant because of small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest the use of an omentum ap to decrease the risk of lymphocele relapse, but others do not [3±5, 14,30]. Recently, laparoscopic fenestration of posttransplant lymphoceles has been reported in the literature (Table 4) [1,6,8,9,11,15,16,19,25,28,31,32,36,38].…”
Section: Discussionmentioning
confidence: 96%
“…Hsu et al, in a multicenter review of experienced centers, found a complication rate of 5% with only a single urinary tract (bladder) injury (8). Cadrobbi et al (20) found a 7% incidence of urinary tract injury (renal pelvis, ureter, bladder) with laparoscopic fenestration, but the rate was lower in centers with significant experience.…”
Section: Discussionmentioning
confidence: 99%